The factor in influencing the selection of simpanan shariah fund of epf among staff epf Alor Setar Kedah / Kamil Naim Hairuddin - Hairuddin, Kamil Naim
The purpose of this research is want to to study the factor influencing the selection of simpanan shariah fund of EPF among staff EPF Alor Setar. The study analyzed the static and numerical data from a survey of 99 participation of staff in EPF Alor Setar range age 18-62 years old. The questionnaire consists of 34 question divided by 6 sections which is demographic of respondents, the selection of the fund, the perception of fund commitment to shariah compliant, the perception of risk tolerance, the perception of size of the fund and the perception of past performance. Basically, the main reason why EPF staff choose to contribute in simpanan shariah is to follow the Islamic teaching. The finding of this study is that EPF staff didn’t want their source of money coming from something that is not halal.